A history of childhood maltreatment is associated with altered DNA methylation levels of DNA methyltransferase 1 in maternal but not neonatal mononuclear immune cells - Mavioglu, Rezan Nehir; Ramo-Fernandez, Laura; Gumpp, Anja M.; Kolassa, Iris-Tatjana; Karabatsiakis, Alexander (Frontiers in Psychiatry, 2022)
Childhood maltreatment (CM) is associated with alterations in DNA methylation (DNAm) especially in stress response genes. Due to the higher risk of overall health complications of individuals with a parental history of CM, intergenerational transmission of CM-associated DNAm changes has been investigated but remains unclear. In this study, we investigated if different severities of CM have any influence on the DNAm of DNA methyltransferase 1 (DNMT1), an important enzyme of the DNAm machinery, in immune and buccal cells of mother-newborn dyads. DNAm was assessed by mass spectrometry using immune cell DNA from mothers (N = 117) and their newborns (N = 113), and buccal cell DNA of mother-newborn dyads (N = 68 each). Mothers with a history of CM had lower mean methylation of DNMT1 in immune cells compared to the mothers without a CM history. CM status only influenced maternal DNMT1 gene expression when at least moderate CM was reported. Buccal cell DNAm was not associated with CM status. Maternal history of CM was not linked to any alterations in DNMT1 mean DNAm in any of the cell types studied in newborns. We conclude that the CM-associated alterations in DNMT1 DNAm might point to allostatic load and can be physiologically relevant, especially in individuals with more severe CM experiences, resulting in an activated DNA methylation machinery that might influence stress response genes. Our lack of significant findings in buccal cells shows the tissue-specific effects of CM on DNAm. In our sample with low to moderate maternal CM history, there was no intergenerational transmission of DNMT1 DNAm in newborns.